Pediatric surgical rib fixation: A collected case series of a rare entity. Issue 6 (December 2021) - Polycarpou, Andreas; Kim, Brian D.
Abstract : BACKGROUND: Rib fractures are uncommon in children and are markers of extreme traumatic force from high-energy or nonaccidental etiology. Traditional care includes nonoperative management, with analgesia, ventilator support, and pulmonary physiotherapy. Surgical stabilization of rib fractures (SSRFs) has been associated with improved outcomes in adults. In children, SSRF is performed and its role remains unclear, with data only available from case reports. We created a collected case series of published pediatric SSRF cases, with the aim to provide a descriptive summary of the existing data. METHODS: Published cases of SSRF following thoracic trauma in patients younger than 18 years were identified. Collected data included demographics, injury mechanism, associated injuries, surgical indication(s), surgical technique, time to extubation, postoperative hospital stay, and postoperative follow-up. RESULTS: Six cases were identified. All were boys, with age range 6 to 16 years. Injury mechanism was high-energy blunt force in all cases, and all patients suffered multiple associated injuries. Five of six cases were related to motor vehicles, and one was horse-related. Indication(s) for surgery included ventilator dependence in five, significant chest deformity in two, and poor pain control in one case. Plating systems were used for rib stabilization in five of six cases, while intramedullary splint was used in one. All patients were extubated within 7 days following SSRF, and all were discharged by postoperative Day 20. On postoperative follow-up, no SSRF-related major issues were reported. One patient underwent hardware removal at 2 months. CONCLUSION: Surgical stabilization of rib fractures in children is safe and feasible, and should be considered as an alternative to nonoperative therapy in select pediatric thoracic trauma cases. Potential indications for SSRF in pediatric patients include poor pain control, chest wall deformity, or ventilator dependence. Further studies are needed to establish the role and possible benefits of SSRF in pediatric thoracic trauma. LEVEL OF EVIDENCE: Collected case series, level V.